Analisis Konsistensi Implementasi Penggunaan Website pada Proses Rekrutmen dan Seleksi Karyawan Base on Seven Tools Aporoach Method (Studi Kasus PT. Duta Nichirindo Pratama) - Sumaedi, Ade (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
PT. Duta Nichirindo Pratama is an organization engaged in Autoparts Manufacturing, in this research it focuses on analyzing problems in the personnel department, especially the recruitment and selection process for employees. The previous year the recruitment and selection process for employees was still doing manual queuing and the accumulation of job application letter documents that had the potential to generate waste, from this problem the personnel department immediately made improvements by designing a digital computing website using VB.NET, My.SQL server management and PHP programming language, designed to be a Website Link, namely https://dnp.co.id/employeeactivity. Judging from the problems and improvements that have been made, the title determined in this study is "Analysis of the Consistency of the Implementation of Website Usage in the Recruitment and Selection Process of Base On Seven Tools Aporoach Method". The results of the research on the data before and after repairing the waste management of former application documents showed a decrease of 100%, this data analysis used seven quality stone tools (seven Tools Approach) namely check sheet data, bar charts, Pareto diagrams, fishbon diagrams, scatter diagrams, pie charts, histograms. The waste data of former application documents before repairs in the recruitment process for the period January to December 2020 amounted to 183, using 3660 sheets of paper, the number of employees needed is 16 people, the amount of paper needed is 400 sheets, so a cover letter which is disposed of as waste is 3260 pieces or 17 kg. After repairs were made by designing a digital computing website, the application letter which was disposed of as waste per September 2021 to March 2022 was 0 Pcs/sheet.